Modeling and predicting the backstroke to breaststroke turns performance in age-group swimmers - Chainok, P.; de Jesus, K.; Coelho, L.; Ayala, H. V. H.; de Castro Ribeiro, M. G.; Fernandes, R. J.; Vilas-Boas, J. P. (Sports Biomechanics, 2021)
The purpose of the present study was to identify the performance determinant factors predicting 15-m backstroke-to-breaststroke turning performance using and comparing linear and tree-based machine-learning models. The temporal, kinematic, kinetic and hydrodynamic variables were collected from 18 age-group swimmers (12.08 ± 0.17 yrs) using 23 Qualisys cameras, two tri-axial underwater force plates and inverse dynamics approach. The best models were obtained: (i) with Lasso linear model of the leave-one-out cross-validation in open turn (MSE = 0.011; R2 = 0.825) and in the somersault turn (MSE = 0.016; R2 = 0.734); (ii) the Ridge of the leave-one-out cross-validation (MSE = 0.016; R2 = 0.763) for the bucket turn; and (iii) the AdaBoost tree-based model of the leave-one-out cross-validation for the crossover turn (MSE = 0.016; R2 = 0.644). Model`s selected features revealed that optimum turning performance was very similarly determined for the different techniques, with balanced contributions between turn-in and turn-out variables. As a result, the relevant feature`s contribution of each backstroke-to-breaststroke turning technique are specific; developing approaching speed in conjunction with proper gliding posture and pull-out strategy will result in improved turning performance, and may influence differently the development of specific training intervention programmes.